Предмет: Алгебра,
автор: вдадпдпдад
(x2-2x+3)(x2-2x+1)=24
как решить??
Ответы
Автор ответа:
0
(x²-2x+1)*(x²-2x+3)=24
замена переменной: x²-2x+1=t, тогда x²-2x+3=t+2
t*(t+2)=24
t²+2t-24=0
t₁=-6, t₂=4
обратная замена:
t₁=-6, x²-2x+1=-6, x²-2x+7=0. D<0 корней нет
t₂=4, x²-2x+1=4. x²-2x-3=0
x₁=-1. x₂=3
замена переменной: x²-2x+1=t, тогда x²-2x+3=t+2
t*(t+2)=24
t²+2t-24=0
t₁=-6, t₂=4
обратная замена:
t₁=-6, x²-2x+1=-6, x²-2x+7=0. D<0 корней нет
t₂=4, x²-2x+1=4. x²-2x-3=0
x₁=-1. x₂=3
Похожие вопросы
Предмет: Информатика,
автор: zhenya210989
Предмет: Геометрия,
автор: bogdanai1234
Предмет: Алгебра,
автор: dias180607
Предмет: Алгебра,
автор: andrey5539
Предмет: История,
автор: arsenteva021